2011
DOI: 10.1016/j.jtcvs.2011.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Cone reconstruction of the tricuspid valve in Ebstein anomaly with or without one and a half ventricle repair

Abstract: Addition of a bidirectional cavopulmonary shunt to cone reconstruction of the tricuspid valve should be considered for young patients with severe Ebstein anomaly who are at high risk of right ventricular failure after the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 16 publications
(19 reference statements)
2
24
2
2
Order By: Relevance
“…There is a general consensus that operative mortality in Ebstein's anomaly has been reduced dramatically with the introduction of a bidirectional superior cavopulmonary anastomosis in association with tricuspid valve repair . Various preoperative and intraoperative parameters, including right ventricular morphology and function, preoperative cyanosis, postoperative right atrial pressure, functional tricuspid orifice size, and postoperative hemodynamic instability, have been suggested to indicate the need for an additional bidirectional superior cavopulmonary anastomosis. There are also pitfalls of the bidirectional superior cavopulmonary anastomosis, such as facial edema and upper extremity numbness (particularly in the morning), jugular vein engorgement, headache, central venous thrombosis, and vascular inaccessibility through the superior vena cava to the heart.…”
Section: Discussionmentioning
confidence: 99%
“…There is a general consensus that operative mortality in Ebstein's anomaly has been reduced dramatically with the introduction of a bidirectional superior cavopulmonary anastomosis in association with tricuspid valve repair . Various preoperative and intraoperative parameters, including right ventricular morphology and function, preoperative cyanosis, postoperative right atrial pressure, functional tricuspid orifice size, and postoperative hemodynamic instability, have been suggested to indicate the need for an additional bidirectional superior cavopulmonary anastomosis. There are also pitfalls of the bidirectional superior cavopulmonary anastomosis, such as facial edema and upper extremity numbness (particularly in the morning), jugular vein engorgement, headache, central venous thrombosis, and vascular inaccessibility through the superior vena cava to the heart.…”
Section: Discussionmentioning
confidence: 99%
“…3 Since the first reported cases of the BDG in patients with Ebstein's malformation, 14 few reports have demonstrated that the addition of a BDG to the TV repair decreases mortality. [1][2][3][4][5][6][15][16][17] The BDG in the setting of RV failure: (1) reduces the venous return to the enlarged, dysfunctional RV and (2) optimizes the LV preload. The construction of a BDG in patients with moderate or severe TVR reduces the regurgitation grade, allowing less aggressive TV interventions, 5 and decreasing the incidence of reoperation in patients with residual TVR.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical therapy for Ebstein's malformation should restore TV competence and address the inadequacy of the inefficient RV. All the reported surgical strategies have in common the detachment and reimplantation of the major leaflets and complete plication of the atrialized portion of the RV …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, even in the presence of these risk elements, the cone technique can be applied, according to Liu et al 4 in 30 of these patients, of which in 20 of them Glenn's bidirectional procedure was also employed concurrently (1,5 ventricle repair) vis-à-vis marked dilatation and right ventricular dysfunction, in an average age of 60 months (ranging from 2 to 192 months). The results obtained by these authors 4 were also satisfactory, with reappearance of moderate to severe tricuspid regurgitation in four (13.3%) patients, with one death (3.3%). As already shown, Glenn's bidirectional operation is useful in combination with the cone plastic surgery in the presence of ventricular dysfunction, and cardiac transplantation is employed in rare extreme cases of ventricular dysfunction associated.…”
mentioning
confidence: 99%